2020
DOI: 10.1111/epi.16699
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal developmental and epileptic encephalopathy due to autosomal recessive variants in SLC13A5 gene

Abstract: Objective: Autosomal recessive pathogenic variants of the SLC13A5 gene are associated with severe neonatal epilepsy, developmental delay, and tooth hypoplasia/hypodontia. We report on 14 additional patients and compare their phenotypic features to previously published patients to identify the clinical hallmarks of this disorder. Methods: We collected clinical features of 14 patients carrying biallelic variants in SLC13A5 and performed a PubMed search to identify previously published patients. Results: All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 23 publications
(159 reference statements)
3
52
1
Order By: Relevance
“…Functional impacts of NaCT inhibition or knockdown have been proposed in cells, though findings are not necessarily dependent on the presence of extracellular citrate (Li et al, 2017;Phokrai et al, 2018;Poolsri et al, 2018). Citrate transport may also influence AcCoA metabolism and ionic homeostasis in the nervous system, as loss-of-function mutations in SLC13A5 have been linked to pediatric epilepsy, Kohlschütter-Tönz syndrome, and other brain disorders (Hardies et al, 2015;Klotz et al, 2016;Matricardi et al, 2020;Schossig et al, 2017;Thevenon et al, 2014). Notably, citrate levels were significantly increased in plasma and cerebrospinal fluid (CSF) in such epilepsy patients (Bainbridge et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Functional impacts of NaCT inhibition or knockdown have been proposed in cells, though findings are not necessarily dependent on the presence of extracellular citrate (Li et al, 2017;Phokrai et al, 2018;Poolsri et al, 2018). Citrate transport may also influence AcCoA metabolism and ionic homeostasis in the nervous system, as loss-of-function mutations in SLC13A5 have been linked to pediatric epilepsy, Kohlschütter-Tönz syndrome, and other brain disorders (Hardies et al, 2015;Klotz et al, 2016;Matricardi et al, 2020;Schossig et al, 2017;Thevenon et al, 2014). Notably, citrate levels were significantly increased in plasma and cerebrospinal fluid (CSF) in such epilepsy patients (Bainbridge et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Biallelic LoF variants in SLC13A5 cause DEE25 characterized by neonatal‐onset epilepsy with fever‐sensitivity, recurrent status epilepticus, global developmental delay/intellectual disability in addition to variable neurological features including ataxia, microcephaly, choreoathetosis and spasticity (Hardies et al, 2015; Klotz et al, 2016; Kopel et al, 2017; Matricardi et al, 2020; Schossig et al, 2017; Thevenon et al, 2014). The three affected siblings have the aforementioned features with profound GDD/ID although only one affected child, the eldest (BAB12492), had microcephaly (defined as OFC < −2 SD ) while the other two had borderline microcephaly (−1.65 SD and z = −1.95 SD ) thus fitting into the spectrum of SLC13A5 ‐related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto et al [2017], Wang et al [2017], Stringer et al [2020] and Brenner et al [2019 demonstrated that that the expression of SPP1, C5AR1, CACNA1H and CACNA1A are associated with the prognosis of amyotrophic lateral sclerosis, but these genes might be associated with advancement of dementia. TGFBR1 [Zheng et al 2021], SCN4A [Bergareche et al 2015], KCNT1 [McTague et al 2018], SLC13A5 [Matricardi et al 2020] and CACNA1B [Gorman et al 2019] were reported to be associated with progression of epilepsy, but these genes might be involved in dementia.…”
Section: Discussionmentioning
confidence: 99%